Entre riscos, narrativas e lembranças: esboço de uma memória coletiva da arte de rua em João Pessoa - Cunha, Thiago da Silveira (2019)
The graffiti and the pixação have long been present in the history of cities. They inscribe popular yearnings, poetry, feelings, itineraries, chronicles, memories. Far beyound the content displayed on the wall, this work seeks to reach your creators and your narratives. In general, this effort communes with the political proposal of the Cultural Studies, toning the voices of peripheral characters and your underground memories (POLLAK, 1989). The movement undertaken aims to make them the authors of theirs own collective memory. I perform a critique from his narratives, exploring the relations between literature, memory and orality. I bring some of the marks related to this urban movement and discuss the approximations and distances between graffiti and pixação over time from their own internal fissures and memory regimes. Besides that, I confront them with what the official institutions publish and say about that, evidencing their creative movements of subversion of the language, both in its spelling - piXação - and in the level of adjectivation. In this perspective, the official narratives usually associate these inscriptions with dirt and vandalism, words positivated by their agents. The reflection about memory deepens the links between subjectivation and remembrance, as from devices fired by Deleuze and Guattari (1972; 1992). Under this bias, the visual anthropology assists the analysis of these folds in the body, in the voice and in the situation of the oral narrative (ZUMTHOR, 1997). Thereby, the exercise of criticism can meet the requisites required in its work, reaching a balance between form and content, text and context (EAGLETON, 2001; SARLO, 1997). The methodological reflection carried out has on emphasis on field experience. Thereat, I try to contribute and encourage the researches on orality carried out in the area of literature by the “critics-ethnographers” who aim to go to the physical meet of the other, exercising a human listening and capturing narratives that, if it were not for this effort, would only hear about it. Converging with the hypothesis of Paul Zumthor (1997), it was possible to recognize in the testemunies of the graffiti and pixação writers innumerables narrative genres, finding well-developed storys from the literary point of view. This destabilizes the literary object and the canon, revealing a singular richness provided by the daily voices.